1995
DOI: 10.1093/ajcp/103.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Virus-associated Hemophagocytic Syndrome Characterized by Clonal Epstein-Barr Virus Genome

Abstract: Virus-associated hemophagocytic syndromes are a heterogeneous group of disorders in which viral infection is associated with a proliferation of hemophagocytic histiocytes throughout the reticuloendothelial system. The authors report the case of a 24-year-old Vietnamese male who developed a hemophagocytic syndrome associated with Epstein-Barr virus (EBV) and who died following a rapidly progressive course. A proliferation of reactive-appearing lymphoid cells was associated with an extensive proliferation of ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…We retrospectively analyzed 20 cases diagnosed with either EBV-HLH or EBV-related diseases with the clinical signs and symptoms of HLH. The latter cases mostly involved FIM and EBV-NK-LAHS, which are often complicated with hemophagocytosis [1,[8][9][10]. For example, Mroczek et al [2] have shown that 43 of 52 patients with FIM (80%) had clinicopathologic features of hemophagocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We retrospectively analyzed 20 cases diagnosed with either EBV-HLH or EBV-related diseases with the clinical signs and symptoms of HLH. The latter cases mostly involved FIM and EBV-NK-LAHS, which are often complicated with hemophagocytosis [1,[8][9][10]. For example, Mroczek et al [2] have shown that 43 of 52 patients with FIM (80%) had clinicopathologic features of hemophagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Information on the literature cases was obtained only by the article content, not through contact with the authors. As a result, only 9 cases were eligible [1,5,6,[9][10][11][27][28][29]. The eligible criteria for inclusion in this study were: (a) the age at disease onset of the patient was between 15 and 34, (b) the diagnosis was EBV-HLH, or an EBV-related disease with the clinical signs and symptoms of HLH [35], and (c) information on the treatment, particularly the timing of etoposide administration as well as outcome was available.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several approaches to determine the relationship between individual EBV strains and EBV-related diseases such as malignant lymphoma, 27 nasopharyngeal carcinoma, 28 Burkitt lymphoma, 29 and gastric carcinoma 30 have been reported. The significance of type B in the immunocompromised host in Western countries 27 and the variants of EBNA-1 C-terminal region have been suggested.…”
Section: Discussionmentioning
confidence: 99%